A continuous arc delivery optimization algorithm for CyberKnife m6. Issue 8 (21st June 2018) - Kearney, Vasant; Descovich, Martina; Sudhyadhom, Atchar; Cheung, Joey P.; McGuinness, Christopher; Solberg, Timothy D.
Abstract : Purpose: This study aims to reduce the delivery time of CyberKnife m6 treatments by allowing for noncoplanar continuous arc delivery. To achieve this, a novel noncoplanar continuous arc delivery optimization algorithm was developed for the CyberKnife m6 treatment system (CyberArc‐m6). Methods and Materials: CyberArc‐m6 uses a five‐step overarching strategy, in which an initial set of beam geometries is determined, the robotic delivery path is calculated, direct aperture optimization is conducted, intermediate MLC configurations are extracted, and the final beam weights are computed for the continuous arc radiation source model. This algorithm was implemented on five prostate and three brain patients, previously planned using a conventional step‐and‐shoot CyberKnife m6 delivery technique. The dosimetric quality of the CyberArc‐m6 plans was assessed using locally confined mutual information (LCMI), conformity index (CI), heterogeneity index (HI), and a variety of common clinical dosimetric objectives. Results: Using conservative optimization tuning parameters, CyberArc‐m6 plans were able to achieve an average CI difference of 0.036 ± 0.025, an average HI difference of 0.046 ± 0.038, and an average LCMI of 0.920 ± 0.030 compared with the original CyberKnife m6 plans. Including a 5 s per minute image alignment time and a 5‐min setup time, conservative CyberArc‐m6 plans achieved an average treatment delivery speed up of 1.545x ± 0.305x compared with step‐and‐shoot plans. Conclusions: The CyberArc‐m6 algorithm was able to achieve dosimetrically similar plans compared to their step‐and‐shoot CyberKnife m6 counterparts, while simultaneously reducing treatment delivery times.